The history of resource mobilization and social spending in Uganda - Marianne S. Ulriksen; Mesharch W. Katusiimeh (United Nations Research Institute for Social Development (UNRISD), 2014)
This paper is the first of a series of papers exploring the political and institutional contexts of resource mobilization and social spending for social development in Uganda. We provide the historical context of, and trends in, resource mobilization (domestic and external revenue) and social spending in post-independence Uganda. After years of civil war, mismanagement and general decline, Uganda turned a page in 1986 when NRM (National Resistance Movement) came to power. During the 1990s and early 2000s, Uganda was a prototypical donor-dependent country with aid constituting more than half of government revenue. During this period, the government, in partnership with donors, focused spending on targeted pro-poor development programmes, including primary education and basic health care. While priority of these social sectors has led to some improvements in social development outcomes, the quality of education and health care is still disappointing and social protection programmes remain neglected. Moreover, domestic resource mobilization has not improved considerably which points to issues of weak institutional capacity as well as the contested nature of taxation. Trends in recent years show an increasingly strained relationship between the government and its traditional donors, piecemeal and ad hoc tax reforms, promise of increasing revenue from oil, and a move in policy priorities away from human capital development to spending on infrastructure and expansion of productive sectors.
Keywords: 330